The Influence of Perception of the Teaching Profession, Self-Efficacy of Natural and Social Sciences Subjects and Family Environment on Interest in Becoming an Elementary School Teacher - Jumiati Jumiati (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the influence of the perception of the teaching profession, self-efficacy of the science subjects, and family environment on the interest of students of the Elementary School Teacher Education Study Program (PGMI) to become (MI) Elementary School teachers. The study used a quantitative approach with a survey method. The study population consisted of 52 PGMI fifth semester students, with a sample of 34 students selected using a purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the help of SPSS version 25. The results showed that partially the perception of the teaching profession and self-efficacy of the science subjects did not significantly influence the interest in becoming MI teachers. In contrast, the family environment had a positive and significant influence on students' interest in pursuing the MI teaching profession. However, simultaneously the perception of the teaching profession, self-efficacy of the science subjects, and the family environment significantly influenced the interest in becoming MI teachers. These findings indicate that interest in becoming MI teachers is formed through the interaction of psychological, academic, and social factors, with the family environment as the most dominant factor. This study provides important implications for the PGMI study program in designing a more holistic and contextual strategy for developing prospective teachers.